Psychometric Properties of the Jordanian Version of the ‎Wide Range Assessment for Memory and Learning ‎‎(WARAML2) for the Age Group (5-8) Years‎ - Dabos ‎, Maha; Abu Awwad, Ferial (Jordan Journal of Educational Sciences, 2019)
This study aimed to investigate the psychometric characteristics of a Jordanian version of wide range assessment for memory and learning - second edition, for Sheslow and Adams WRAML2. To achieve the aim of this study, the instructions for the application of the test battery were translated, as well as, the items of the tests, according to the culture of Arab countries and Jordan in particular. The study used the descriptive survey method, based on the randomized multi-stage sampling method. The sample consisted of (600) children; ranging in age between (5-8) years, who were randomly selected from different regions in Jordan (North, Central and South). The results of construct validity through exploratory factorial analysis showed that there were three factors explained (60.934%) of the total variance. Results also showed statistical differences in wide range assessment for memory and learning, according to age variable. The results concluded that the scale has appropriate reliability index, which was calculated using test- retest reliability, values ​​ranged between (0.654 to 0.866), and by using Chronbach Alpha, values ​​ranged between (0.63 to 0.94).